Does Confucianism prompt firms to participate in poverty alleviation campaigns? - Huang, Min (Journal of business ethics, 2024)
This study examines the influence of Confucianism on corporate poverty alleviation (PA) participation. We argue that firms in regions with more Confucian temples are more likely to participate in government-initiated PA programs because Confucianism emphasizes common social welfare. This positive relationship is stronger for firms with chief executive officers born in Confucian regions and for firms that are under high media pressure, as the trade-off between social welfare and firm interest is in favor of Confucianism. Using a sample of Chinese-listed firms, we find evidence supporting our arguments. Moreover, we find consistent evidence that firms influenced by Confucianism are motivated to pay long-term attention to PA activities and improve corporate PA efficiency, highlighting the substantive role of Confucianism in a PA campaign. Our study contributes to the business ethics literature by introducing Confucianism into research on corporate social activities and provides practical implications.